2015
DOI: 10.1016/j.solmat.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient selective metamaterial absorber for high-temperature solar thermal energy harvesting

Abstract: ABSTRACT:In this work, a metamaterial selective solar absorber made of nanostructured titanium gratings deposited on an ultrathin MgF 2 spacer and a tungsten ground film is proposed and experimentally demonstrated. Normal absorptance of the fabricated solar absorber is characterized to be higher than 90% in the UV, visible and, near infrared (IR) regime, while the mid-IR emittance is around 20%. The high broadband absorption in the solar spectrum is realized by the excitation of surface plasmon and magnetic po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
134
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(135 citation statements)
references
References 30 publications
0
134
1
Order By: Relevance
“…The 2D array from ref. [ 107 ] A comprehensive investigation of the dependence of absorption on the polar and azimuthal angles of the incident wave was conducted as well. [ 75 ] , but works for both TE and TM polarizations.…”
Section: D Slab Arraysmentioning
confidence: 99%
“…The 2D array from ref. [ 107 ] A comprehensive investigation of the dependence of absorption on the polar and azimuthal angles of the incident wave was conducted as well. [ 75 ] , but works for both TE and TM polarizations.…”
Section: D Slab Arraysmentioning
confidence: 99%
“…Recently, the plasmonic metamaterial absorbers based on the surface plasmon resonance (SPR) have attracted increasing attention due to their potential extensive applications in energy harvesting [13], hot-electron collection [47], thermal emitters [811], and biosensors [1217]. Up to date, various plasmonic metamaterial absorbers have been proposed in different wavebands, which are mainly divided into two main categories: broadband absorbers and narrowband absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, W and SiO 2 are chosen as the base materials of the solar absorber owing to their thermal stability at high temperatures. 28,39 The nanopores of the structure are to reduce the effective refractive index of this absorber, which can achieve a better impedance match to free space. The rst SiO 2 layer coated onto the structure is operating as an antireective material, which is to further reduce the impedance mismatch.…”
Section: Resultsmentioning
confidence: 99%
“…8 To our knowledge, the reported selective solar absorption are mainly realized by these broadband absorbers based on the nanostructures constructed by arraying different nano-sized resonators in one plane to combine multiple plasmonic resonances. [38][39][40][41][42][43][44][45] For example, Aydin et al proposed and demonstrated a plasmonic absorber capable of selective high absorption over the visible spectrum(400-700 nm) owing to the symmetric arrangement of crossed trapezoid array geometry. 37 However, this absorber only can realize broadband high absorptions in the visible region and cannot satisfy the spectral requirements for solar energy absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation